Hubungan Penyesuaian Diri dengan Stres Akademik pada Siswa - Korengkeng, Loura; Iman, Dian Pratiwi; Najoan, Santi (Universitas Malahayati, 2023)
ABSTRACT Self-adjustment is an important requirement for the creation of individual mental health. Many students feel burdened and unable to achieve happiness in their lives due to their inability to adapt, one of which is the school transition. Academic stress is a problem faced by students. This study aims to determine the relationship between self-adjustment and academic stress among students at Dewi Laut Bitung Highschool. This study uses a descriptive correlational method with a cross-sectional approach. The sampling technique used total sampling with a sample size of 71. Data was collected using self-adjustment and academic stress questionnaires. Data analysis showed that the majority of participants, 52 respondents (70.4%), had moderate self-adjustment, and 47 respondents (66.2%) had moderate academic stress. Further data analysis using Pearson correlation showed a value of p=0.001; and r=-0.370. There is a significant relationship between self-adjustment and academic stress among students at SMK Dewi Laut Bitung. The relationship was found to be weak with a negative direction, indicating that the higher the participants' self-adjustment, the lower their academic stress. It is recommended for SMK Dewi Laut Bitung school authorities to pay attention to stress management by creating a pleasant and communicative learning environment, allowing students to participate in the learning process effectively. For future researchers, it is recommended to conduct research on improving the self-adjustment of students at SMK Dewi Laut Bitung regarding academic stress through guidance and counseling. Keywords: Self-Adjustment, Academic Stress, Students ABSTRAK Penyesuaian diri merupakan persyaratan penting bagi terciptanya kesehatan jiwa individu. Banyak siswa merasa terbebani dan tidak mampu mencapai kebahagiaan dalam hidupnya karena ketidakmampuan dalam menyesuaikan diri, salah satunya adalah transisi sekolah. Stres akademik merupakan permasalahan yang dihadapi peserta didik. Penelitian ini bertujuan untuk mengetahui hubungan penyesuaian diri dengan stres akademik pada siswa SMK Dewi Laut Bitung. Penelitian ini menggunakan metode deskriptif korelasi dengan pendekatan cross sectional. Teknik pengambilan sampel menggunakan total sampling dengan jumlah 71 sampel. Data dikumpulkan menggunakan kuesioner penyesuaian diri dan stress akademik. Analisis data menunjukan bahwa sebagian besar partisipan yaitu 52 responden (70.4%) memiliki penyesuaian diri sedang dan 47 responden (66.2%) memiliki stres akademik sedang. Lebih lanjut analisis data menggunakan pearson correlation menunjukkan nilai p= 0.001; dan r= - 0.370. Terdapat hubungan yang signifikan antara penyesuaian diri dengan stres akademik pada siswa SMK Dewi Laut Bitung. Hubungan ditemukan pada kategori lemah dengan arah negative, yangmana semakin tinggi penyesuain diri partisipan maka semakin rendah stres akademik yang dimiliki. Direkomendasikan bagi pihak sekolah SMK Dewi Laut Bitung untuk dapat memperhatikan penanganan stres dengan menciptakan suasana belajar yang menyenangkan dan komunikatif sehingga siswa boleh mengikuti proses pembelajaran dengan baik. Bagi peneliti selanjutnya direkomendasikan untuk melakukan penelitian dengan peningkatan penyesuaian diri siswa SMK Dewi Laut Bitung terhadap stres akademik melalui bimbingan dan konseling. Kata Kunci: Penyesuaian Diri, Stres Akademik, Siswa